Penerapan Penghargaan, Pelatihan, dan Komunikasi Internal Meningkatkan Kinerja Pegawai BTPN Syariah Wlingi Blitar - Vinola Ria Ifani; Mariana Puspa Dewi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Employee performance plays a vital role in achieving organizational goals and maintaining competitive advantage in the banking industry. In BTPN Syariah Wlingi Blitar, challenges related to employee motivation, skill development, and effective communication have been identified as key factors affecting performance. This study explores the implementation of rewards, training programs, and internal communication as a strategic approach to improving employee performance in BTPN Syariah Wlingi Blitar. This study uses a qualitative method with a case study approach to analyze the implementation of rewards, training, and internal communication to improve employee performance in BTPN Syariah Wlingi Blitar. The implementation of rewards, training, and internal communication in BTPN Syariah Wlingi Blitar has been proven to have a positive impact on improving employee performance. Rewards in the form of financial and non-financial incentives can motivate employees to work more optimally. Training conducted periodically improves employee competence and ability in carrying out their duties, especially in providing quality service to customers. Effective internal communication creates a harmonious work environment, minimizes miscommunication, and strengthens collaboration between employees.